Analyzing Political Marketing in Indonesia: A Palm Oil Digital Campaign Case Study - Khairiza, Fajrina; Kusumasari, Bevaola (Forestry Faculty, Universitas Hasanuddin, 2020)
Social media in political marketing is an emerging area of research. This study explains how social networks are constructed in a digital campaign, identifying key actors, and messages involved in modern political marketing. A hotly contested palm oil campaign in Indonesia serves as a case study to analyze and visualize the messaging content found in digital campaigns. Social Network Analysis (SNA) was used to map the social network sites in Twitter and to track social interaction patterns in the #SawitBaik campaign. The results confirmed that state institutions, non-governmental institutions, news media, and individuals were key actors in the digital campaign. The actors’ roles varied from providing information and supporting palm oil activities to criticizing palm oil activities and promoting campaign events. Most tweets were critical of the government, serving as brand advocacy. The #SawitBaik campaign is also an example of political marketing used by a government in order to influence its citizens. In this case, the goal was to shape and win public support by legitimizing palm oil activities in Indonesia.